(3GdQhVI GdHgjI aj TQM GddeYI GdOeTbjIs - (3GdYGedj GdLYHj, GdTgjO GdKGfj, Rjf GdOjf Hf Ydj Hf CMeO, (B966 (3g`s
(3ChdgG (B:s
... (3hGdBNQ VYja Ch ehKb aGdQLhY ajgG Edi GdCUhd GdTQYjI Chdi hddeUfa Qg aj GdMce GdKGfj HMK fHg Ydjg Hbhdg (B" (3haj Pdc fXQ dCf bVjI cd ELGOI GdefY ef fbjVgG (B" (3ajecf Cf jLYd ehQO GdELGOI gfG GdbSe (B...s
(3BNQgG (B:s
.. (3aGdCbhi VeGf GdeaQW efge Ohf ZjQg hGdQhGjI McGjI aj hGbYI eMJedI ddJChjd hdjcf gPG BNQ GddeYI hde fPcQ ajgG Shi GdeHge ef GdCMcGe hgh eTghQ Hjf GdCUMGH gPG HMSH GdZGdH (B.. (3hfSCdg ef aVdg hcQegs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B3\ 64s
(3GdPQjYI (B11/209 ( 1757)s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis